Unrecognized esophageal fish bone impaction with delayed presentation of acute spastic central chest pain: A case report. Issue 8 (February 2019) - Liu, Ching-Han; Huang, Shih-Chung; Lin, Wei-Shiang; Lin, Chin-Sheng
Abstract: Rationale: Esophageal chest pain is difficult to be identified, and the diagnosis requires a high index of clinical suspicion. Upon presentation, they are difficult to be differentiated from acute coronary syndrome (ACS) by symptomatology alone. Patient concerns: We report a 71-year-old woman with multiple risk factors for coronary heart disease who presented with acute central spastic chest pain and was diagnosed as ACS in emergency department. Diagnoses: Chest computed tomography revealed 1 radiopaque lesion over the upper-third of the esophagus. One fishbone with 3-pointed heads stuck in the esophagus was noted under esophagogastroscopic examination. Interventions: The fishbone was extracted successfully via endoscopy under general anesthesia. Outcomes: The woman was discharged uneventfully after 3 days' hospitalization. Lessons: This case illustrates that, even in emergency, clinicians should always keep in mind the possibility of esophageal foreign body impaction when confronted with frank central chest pain without associated gastrointestinal symptoms. This holds true even in the scenario of multiple cardiovascular risk factors and absence of ingestion history.